2020
DOI: 10.3390/ma13020398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Imidazoline Inhibitor on the Rehabilitation of Reinforced Concrete with Electromigration Method

Abstract: Steel bars embedded in reinforced concrete are vulnerable to corrosion in high chloride environments. Bidirectional electromigration rehabilitation (BIEM) is a novel method to enhance the durability of reinforced concrete by extracting chloride out of concrete and introducing an inhibitor to the surface of the steel bar under the action of an electric field. During the migration process, a higher ionization capacity of the inhibitor with a symmetrical molecular structure was introduced. A new imidazoline inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…[64] Valcuende et al studied the corrosion resistance of the ultra-high performance concretes (UH) made with different fiber volume contents and under distinct curing conditions and concluded that UHs give excellent performance due to their high resistance to chloride penetration and their excellent resistivity. [65] Naveen Kumar et al have studied to assess the initial corrosion behavior of thermo-mechanically treated rebar (TMT), corrosion resistant rebar (CRS) and fusion bonded epoxy coated rebar (EC) under controlled condition (CC) and in simulated marine environment condition (SME) and concluded that the benefit of EC is anticipated to increase the durability of RC structures, particularly when periodic decay is extended in the regions where chloride accumulation is heavy and at that point deterioration of RC structures will become a considerable fit out. [66]…”
Section: Correlation Between the Natural Process Of Corrosion And The...mentioning
confidence: 99%
“…[64] Valcuende et al studied the corrosion resistance of the ultra-high performance concretes (UH) made with different fiber volume contents and under distinct curing conditions and concluded that UHs give excellent performance due to their high resistance to chloride penetration and their excellent resistivity. [65] Naveen Kumar et al have studied to assess the initial corrosion behavior of thermo-mechanically treated rebar (TMT), corrosion resistant rebar (CRS) and fusion bonded epoxy coated rebar (EC) under controlled condition (CC) and in simulated marine environment condition (SME) and concluded that the benefit of EC is anticipated to increase the durability of RC structures, particularly when periodic decay is extended in the regions where chloride accumulation is heavy and at that point deterioration of RC structures will become a considerable fit out. [66]…”
Section: Correlation Between the Natural Process Of Corrosion And The...mentioning
confidence: 99%
“…In this study, a new imidazoline inhibitor was synthesized containing a symmetrical molecular structure with two imidazoline heterocycles and two alkyl long chains of lauric acid [24]. Synthesis of the imidazoline inhibitor is as follows [25]: Firstly, sulfoxide chloride was dropped into lauric acid and stirred for 1-5 h at 40-80 • C. Once the above reaction was completed, the lauroyl chloride was obtained, and then lauroyl chloride was added to the mixed solution of water containing NaHCO3 and ether before ethylenediamine was dripped. Ethylenediamine bislauroyl amide was obtained by stirring for 6 h at 10-40 • C, and then through filtering out the solid, washing and drying.…”
Section: Synthesis Of the Imidazoline Inhibitormentioning
confidence: 99%
“…The specimens were then placed in a ventilated area for 72 h; after 72 h of standing, most of the residual electricity in the test specimen will dissipate, which will not affect the corrosion potential test results of the steel bars, and the performance of the concrete will also recover to more than 90%; then depolarization treatment was performed and the influence of residual electricity on the steel bars in the concrete after completion of the power supply was assessed for influence on the test results. The electrochemical refractometer 600 (Gamry, Warminster, PA, USA) was used to obtain the potentiometric polarization curve to investigate the effect of triethylenetetramine inhibitors on the corrosion resistance of concrete [25,26].…”
Section: Corrosion Potential Of Rebarmentioning
confidence: 99%